Exploring SRI Intention In Young Investors: Benefit, Norms, and Government Support - Martutiningrum, Dwi; Catyanadika, Putra Endi (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Cirebon, 2025)
Sustainable Responsible Investment (SRI) has gained greater recognition as young investors show increased interest in green issues, incorporating environmental, social and governance (ESG) criteria alongside financial objectives in response to growing concerns about climate crisis, social disparity and governance. This study examines factors influencing SRI intention among young prospective investors in Indonesia by integrating Environmental and Social Concern (ESC), Subjective Norm (SN), and Perceived Government Intervention (PGI), with Perceived Benefit (PB) as both a predictor and mediator. A total of 183 responses were collected through an online questionnaire targeting Indonesian Millennials and Generation Z. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results reveal that PB plays a pivotal role in bridging ESC, SN, and PGI to Pro-Environmental Investing Intention (PEII). These findings imply that perceptions of benefit are essential to fostering sustainable investment intentions. The study contributes by enriching the investment behavior pattern of young generations in the SRI context and offers practical implications for designing policies to increase SRI participation among youth.